P546 Vedolizumab outcomes in real-world bio-naive ulcerative colitis and Crohn's disease patients (EVOLVE) in Canada: Interim results. (16th January 2018) - Bressler, B; Greenup, A -J; Bassel, M; Stein, D; Soni, M; Radulescu, G; Neish, C; Khalid, J M; Demuth, D
Abstract: Background: Vedolizumab (VDZ) is a gut-selective anti-α4β7 integrin indicated for the treatment (Tx) of moderately to severely active ulcerative colitis (UC) and Crohn's disease (CD). Real-world outcomes in patients receiving VDZ as a first-line biologic Tx are limited. This study aims to evaluate real-world Tx patterns, clinical effectiveness and safety among biologic-naive UC and CD patients receiving VDZ in Canada. Methods: This is a retrospective chart review study of UC and CD patients who were biologic-naïve, aged ≥18 years at VDZ initiation (May 19, 2015–December 31, 2016) and had ≥6 months follow-up. Data collection spanned from VDZ Tx initiation to the earliest of death, date site initiated data abstraction or 6 months post-VDZ Tx discontinuation. Reported results are from a descriptive interim analysis of patient demographics and VDZ Tx patterns from two sites. VDZ dose escalation was defined as an increase in infusion frequency (≥2 consecutive infusions) at any point during the Tx period. Tx persistence was calculated using the Kaplan–Meier method. Results: A total of 50 patients (CD: 16; UC: 34) were included in this interim analysis: mean (SD) age, 44.4 (15.5) years, 68.0% male, median (range) disease duration, 5.0 (0.1–35.0) years, median (range) follow-up, 12.9 (6.4–25.5) months. Fifteen patients (30.0%) experienced ≥1 VDZ dose escalation with a median (range) time to first dose escalation of 6.0 (2.7–18.1) months. At 12 months, 38 patients (76.0%) (24 UC [70.6%] and 14 CD [87.5%]) were persistent with VDZ Tx (Figure 1). Overall, 0 (0.0%) and 1 (6.3%) CD patients discontinued due to primary non-response (PNR) and secondary loss of response (SLOR), respectively, and 6 (17.6%) and 4 (11.8%) UC patients discontinued due to PNR and SLOR, respectively. Of 12 patients (24.0%) on concomitant corticosteroids (CS) at Tx initiation, 8 patients (66.7%) discontinued their CS Tx within 12 months. Conclusions: High treatment persistence and low dose escalation rates were observed with VDZ in biologic-naive UC and CD patients. Low rates of discontinuation due to both PNR and SLOR were observed. Two-thirds of patients receiving concomitant CS were able to discontinue their CS during VDZ treatment. These interim data suggest the long-term effectiveness and tolerability of first-line VDZ in UC and CD in real-world clinical practice.